CULTURAL ADAPTATION OF THE CRITICAL NURSING SITUATION INDEX FOR THE BRAZILIAN CULTURE - Anderson Neri Guido; Edinêis de Brito Guirardello (Universidade Federal do Paraná, 2018)
Objective: to translate and adapt the Critical Nursing Situation Index for the Brazilian culture. Method: methodological study that used the stages of translation, synthesis of translations, back-translation, evaluation by committee of judges and pre-test with the participation of 30 nurses. Performed in the period from August 2016 to April 2017 in an Intensive Care Unit in the city of Campinas-SP. Results: the Brazilian version of the instrument was obtained. Assessment of semantic, idiomatic, cultural and conceptual equivalence by the committee resulted in a concordance rate ≥80%. Of the 84 items that comprise the instrument, four underwent modifications. The mean completion time of the instrument in the pre-test stage was 16.7 minutes (Standard deviation ±7.4). Conclusion: The methodological process of translation and cultural adaptation of the Critical Nursing Situation Index was completed successfully, and the instrument presented a satisfactory degree of global comprehension and applicability.